Development and future prospects of 3D printed surimi products: A review - Dieynabou Diao; Ruizhi Yang; Yijin Liu; Yadong Zhao; Meiling Chen; Yan Chen; Bin Zheng; Heng Yen Khong (Applied Food Research)
As one of the dominant seafood products in the global market, consumers appreciate high-quality surimi products for their high nutritional value and unique taste. However, most surimi products on the market need appeal and attractiveness. Recently, the custom design of surimi products using 3D printing technology has been shown to not only make the surimi products more appealing but also to further extend their application in special diets. Although numerous studies have been conducted to optimize surimi inks, control 3D printing parameters, and develop post-processing techniques for 3D-printed surimi products, there are few reviews that collectively summarize the latest advances in the field of surimi 3D printing. This review presents an overview of the progress in 3D printing technology related to surimi and its products to fill the gap. It discusses the suitability of surimi as a 3D printing material, ink properties and printability, and innovative 3D to 6D printing techniques for surimi products. This review provides a basis for developing the application of 3D printing technologies in the food industry.